The Meaning of Rejang Pingit Dance Performance at Geriana Kangin Village, Karangasem, Bali in the Global Era - Ruastiti, Ni Made (Bina Nusantara University, 2018)
This research was compiled from the research results that aimed to understand the meaning of Rejang Pingit dance performance in the global era. This research was conducted because of the imbalance between assumptions and reality in real life. The people who lived in the global era should be more interesting with beautiful performances that were simply performed. However, the fact was different. Although Rejang Pingit dance was very simple, people of Geriana Kangin village preserved it. The question was what was the form of the Rejang Pingit dance performance, what was the meaning contained in the performance? This research used the qualitative method. The data sources of this research were Pingit Rejang dance performance, related informants, journals, and previous research results. All data that had been collected were analyzed using aesthetic theory, religious theory, and the theory of power relations. The results show that Rejang Pingit dance is performed in the form of dance off (with no play). It can be seen from the way of presentation, choreography, performance structure, dressing, makeup, and musical accompaniment of the performance. People of Geriana Kangin village continue to preserve Rejang Pingit dance because it is considered to have the meaning of aesthetic, religious, social, and cultural. Their belief in the myth of the essence of life that undergoes the Rejang Pingit dance is so strong so that they still preserve the dance up to now.